Intellectual and politica trajectory of a socialista professional: the civil engineer Emilio Dickmann (Estudios Sociales, 2018)
The participation of graduates and professors in the Argentinian Socialist Party has been important since its foundation at the end of the 19th century. Being a professional was a condition for accessing to the legal functions of the party in its governing bodies, as well as in areas of knowledge production such as society and economy. This article analyzes the professional and academic career of civil engineer Emilio Dickmann in the universities of La Plata and Buenos Aires and his performance in the Socialist Party from the perspective of his intellectual biography. His career reveals commitment features from professionals towards socialism, contributing with their research to build their study devices about society and also the development of their economic plans.
Keywords: intellectual biography; Dickmann; socialism; professionals; engineering